Loricophrya bosporica n. sp. (Ciliophora, Suctorea) epibiont of Desmoscolex minutus (Nematoda, Desmoscolecida) from oxic/anoxic boundary of the Black Sea Istanbul Strait’s outlet area - Sergeeva, Nelli; Dovgal, Igor (Zootaxa, 2016)
A suctorian ciliate Loricophrya bosporica sp. nov. is described from the body surface of nematodes of genus Desmoscolex collected in oxic/anoxic boundary of the Bosporus outlet area of the Black Sea. The new species differs from relative species L. sivertseni by development of its body, which takes no more than half, or a third of the lorica length, absence of crown-like projections at the lorica edge as for adhesive disk. From L. tuba new species differs by considerably shorter stylotheca and prevalence to nematode host instead of echinoderms.